El verbo de las oraciones escindidas: implicaciones teóricas - Linde-Usiekniewicz, Jadwiga (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
The paper discusses some possible implications arising from the fact that in Spanish all kinds of cleft sentences are apparently pseudo-clefts and both the linking verb and the verb of the relative clause may agree with the clefted subject and possibly object.
The verb of cleft sentences: theoretical implications